2017
DOI: 10.3390/su9111891
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technological and Management Options for Accelerating Transformational Changes in Rice and Livestock Systems

Abstract: Agricultural producers grapple with low farm yields and declining ecosystem services within their landscapes. In several instances, agricultural production systems may be considered largely unsustainable in socioeconomic and ecological (resource conservation and use and impact on nature) terms. Novel technological and management options that can serve as vehicles to promote the provision of multiple benefits, including the improvement of smallholder livelihoods, are needed. We call for a paradigm shift to allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Another study conducted in Uruguay, using the same commercial variety El Paso 144, also reported higher cumulative emissions ranging from 208.0 to 249.0 kg CH 4 ha − 1 (Tarlera et al, 2016). In Colombia, a study conducted using the commercial variety FEDEARROZ-60 reported lower cumulative emissions of 7.5 and 19.5 kg CH 4 ha − 1 in 2015 and 2016, respectively (Chirinda et al, 2017). In Brazil, CH 4 cumulative emissions observed for variety IRGA, 424 were 303.0-424.0 kg CH 4 ha − 1 (Zschornack et al, 2016) which was higher than those reported in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Another study conducted in Uruguay, using the same commercial variety El Paso 144, also reported higher cumulative emissions ranging from 208.0 to 249.0 kg CH 4 ha − 1 (Tarlera et al, 2016). In Colombia, a study conducted using the commercial variety FEDEARROZ-60 reported lower cumulative emissions of 7.5 and 19.5 kg CH 4 ha − 1 in 2015 and 2016, respectively (Chirinda et al, 2017). In Brazil, CH 4 cumulative emissions observed for variety IRGA, 424 were 303.0-424.0 kg CH 4 ha − 1 (Zschornack et al, 2016) which was higher than those reported in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies conducted in LAC have reported a decrease in CH 4 emissions for AWD compared to continuous flooding: in Uruguay a 55% decrease was observed [58] and in Brazil a 25-45% decrease was seen with intermittent irrigation [25,29]. A recent study conducted in Colombia reported a 70% decrease [33]. The reduction in CH 4 emissions has been attributed to changes in soil redox conditions [29,59].…”
Section: Water Managementmentioning
confidence: 99%
“…It appears that water pricing mechanisms, whereby water is priced on a volumetric rather than an area basis, were critical factors in incentivizing the wide-spread adoption of AWD in China. Similar proposals have been made to incentivize AWD adoption in LAC [33], however, as is the case in China, a change in the pricing mechanisms would require strong political will.…”
Section: Water Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Latin America has a significant opportunity to accelerate the transformation of its cattle sector through a wide implementation of novel technological options, such as the use of alternative feed options (Chirinda et al, 2017). However, such options require the decisive actions and support of governments at local and national levels and the engagement of both the private sector and all key local institutions (Serna et al, 2017).…”
Section: Targeted Policiesmentioning
confidence: 99%